2011
DOI: 10.1111/j.1096-3642.2010.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and revision of the linyphiid spider genus Solenysa (Araneae: Linyphiidae: Erigoninae)

Abstract: In this paper we carry out a taxonomic revision and phylogenetic analysis of the linyphiid spider genus Solenysa Simon, 1894. A total of 12 species is treated here, including five new species collected from China and Japan: Solenysa akihisai Tu sp. nov., Solenysa lanyuensis Tu sp. nov., Solenysa retractilis Tu sp. nov., Solenysa tianmushana Tu sp. nov., and Solenysa yangmingshana Tu sp. nov. Solenysa circularis Gao, Zhu & Sha, 1993 is a junior synonym of Solenysa protrudens Gao, Zhu & Sha, 1993. We have assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Gaps in taxon sampling result in gaps of 81 associated character transformation, especially for lineages with 82 long history and many accumulated morphological changes (e.g. 83 Arnedo et al, 2009;Tu and Hormiga, 2011). Insufficient sampling 84 may conceal homoplastic changes (Heath et al, 2008; 85 Huelsenbeck and Lander, 2003).…”
mentioning
confidence: 97%
“…Gaps in taxon sampling result in gaps of 81 associated character transformation, especially for lineages with 82 long history and many accumulated morphological changes (e.g. 83 Arnedo et al, 2009;Tu and Hormiga, 2011). Insufficient sampling 84 may conceal homoplastic changes (Heath et al, 2008; 85 Huelsenbeck and Lander, 2003).…”
mentioning
confidence: 97%
“…Other Solenysa species were described successively from other places in Japan, the Chinese mainland, Taiwan, and the Korean Peninsula (see review by Tu and Li 2006). In recent studies, several new species were sorted from the Solenysa collections deposited in the Department of Zoology, National Museum of Nature and Science (ex National Science Museum, Tokyo), Japan (Tu et al 2007, Tu and Hormiga 2011, Ono 2011). Prior to this study, there were five Solenysa species reported from Japan: Solenysa mellotteei Simon, 1894 (type locality: Yokohama, Kanagawa Prefecture), Solenysa akihisai Tu, 2011 (type locality: Hachioji, Tokyo), Solenysa ogatai Ono, 2011 (type locality: Okazaki-shi, Aichi Prefecture), Solenysa partibilis Tu, Ono & Li, 2007 (type locality: Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Ibuki-yama, Shiga Prefecture) and Solenysa reflexilis Tu, Ono & Li, 2007 (type locality: Itsuki-mura, Kumamoto Prefecture). According to results of a phylogenetic analysis based on morphological data, the twelve known Solenysa species were divided into four groups, and the four species from Japan share a complex of genital characters, forming the Solenysa mellotteei group (Tu and Hormiga 2011). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations